(untitled) (Journal of actual problems of jurisprudence, 2018)
In this article rassmotrivayetsya actual problems of regulation of institute of an extradition in the Republic of Kazakhstan. On the basis of the criminal and criminal procedure legislation of the Republic of Kazakhstan delivery of criminals is analyzed theoretical aspects. Legal grounds for regulation of the questions connected with delivery of criminals are the international contracts, the national legislation and the principle of reciprocity. Key words: prestupnost, criminal, delivery of criminals, extradition, fight against crime.